IN SILICO STUDY OF BASELLA ALBA BIOACTIVE COMPOUNDS AS POTENTIAL THERAPY FOR PSORIASIS AGAINST TUMOR NECROSIS FACTOR-α (TNF-α) RECEPTOR - OKTAVRIANA, TRIASARI; KARIOSENTONO, HARIJONO; PURWANTO, BAMBANG; WIDYANINGSIH, VITRI; WASITA, BRIAN; IRAWANTO, MUHAMMAD E.; DIRGAHAYU, PARAMASARI (International Journal of Applied Pharmaceutics, 2025)
Objective: This in silico study aims to explore the bioactive compound of Basella alba as a potential natural alternative by examining its molecular interactions with Tumor Necrosis Factor-α (TNF-α) receptors. While established biological receptors, such as adalimumab, are currently available and provide effective treatment for psoriasis, they are associated with high costs and potential adverse effects. This research emphasizes the novel potential of underexplored Basella alba compounds for psoriasis therapy, potentially offering safer and more affordable alternatives via plant-based compounds, focusing on receptor targets and interactions through molecular docking against the (TNF-α) receptor. Methods: The active compounds of Basella alba were identified and analyzed using Simplified Molecular Input Line Entry System (SMILES) format via the PubChem database. The prediction on anti-psoriatic agents was performed by using Prediction of Activity Spectra for biologically active Substances (PASS). Structure-Activity Relationship (SAR) approach for predicting the bioactive compound activity. Followed by molecular docking using AutoDock Vina to assess binding affinity with the TNF-α receptor (PDB ID: 2AZ5). Results: Basella alba contains 22 active compounds predicted to exhibit antipsoriatic properties based on computational analysis. Based on the structure-activity relationship (SAR) and molecular docking analyses, acacetin, kaempferol, and beta-carotene were selected as key focus compounds due to their promising pharmacological profiles and strong binding affinities to the TNF-α receptor, a central target in psoriasis pathogenesis. PASS prediction revealed that these compounds possessed high Pa values across critical biological activities, including apoptosis agonist, anti-inflammatory, antioxidant, and antipsoriatic properties. Notably, beta-carotene exhibited the highest predicted antipsoriatic potential with a Pa value of 0.910. Molecular docking studies further confirmed their potential, with acacetin demonstrating the strongest binding affinity (-7.5 kcal/mol) among the tested compounds, followed closely by kaempferol and beta-carotene. These ligands also formed stable interactions with key TNF-α residues, such as TYR59, TYR119, and GLY121, indicating their ability to mimic the control ligand’s interaction profile. Conclusion: The findings indicate that certain compounds from Basella alba, including acacetin, kaempferol, and beta-carotene, may be viable candidates for antipsoriatic agents and natural alternatives to conventional TNF-α inhibitors for psoriasis management. Further experimental validation is necessary to confirm these computational predictions.